Profile Of Traditional Jamu Business In Bengkulu City - agung trisusilo; Putri Suci Asriani; Apri Andani (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2019)
This study attempts to make the profile of the